Simulation as a Methodological Strategy in the Faculty of Education at the University of the Basque Country - Gaintza-Jauregi, Zuriñe (Revista Electrónica Educare, 2020)
This article is based on the idea that we learn by doing. Specifically, this research includes the implementation and evaluation process, at the university, of an innovative educational experience based on simulation. The research aims to demonstrate the effectiveness of simulation as a teaching tool at the university teaching studies in primary education. To achieve this goal, university students receive theoretical and practical information on Pedagogical bases of the inclusive school and simulation and teaching techniques. With this, during a course session, the students simulate a tutorial session around the topic of inclusion for a primary school class. A question is asked in an evaluation exercise to determine the results in terms of knowledge acquisition, and, for the simulation assessment, the university students complete a questionnaire. The results show how simulation leads students to assume the role of a primary school teacher, and in their role as a teacher, they acquire the content of the topic and develop social, personal, and professional skills and abilities. The study, therefore, concludes that simulation is an effective methodological strategy in the university studies to train primary education teachers, and it constitutes, in itself, an educational innovation experience during these studies.